Cellular and cytoskeletal alterations of scleral fibroblasts in response to glucocorticoid steroids. (October 2019) - Bogarin, Thania; Saraswathy, Sindhu; Akiyama, Goichi; Xie, Xiaobin; Weinreb, Robert N.; Zheng, Jie; Huang, Alex S.
Abstract: Steroid-induced ocular hypertension can be seen even after trabecular meshwork (TM) bypass/ablation. Thus, the purpose was to investigate steroid-response in cells distal to the TM by using primary scleral fibroblasts. Primary scleral cell cultures were generated using mid-depth scleral wedges from human donor corneo-scleral rims (n = 5) after corneal transplantation. Cells were treated with dexamethasone (DEX; 100 nM) and compared to media (MED)/vehicle (DMSO) controls. Cell size, shape, and migration were studied using the IncuCyte Live-Cell Analysis System. Cytoskeleton was compared using Alexa Fluor-568 Phalloidin and senescence tested by evaluating beta-galactosidase. Western blot comparison was performed for α-SMA, FKBP-51, fibronectin, phospho-myosin light chain, and myocilin. Scleral fibroblasts upregulated FKBP-51 in response to DEX indicating the existence of steroid-responsive pathways. Compared to controls, DEX-treated cells proliferated slower (~50%; p  < 0.01–0.02), grew larger (~1.3-fold; p  < 0.001), and migrated less ( p  = 0.01–0.006). Alexa Fluor 568 Phalloidin actin stress fiber labeling was more diffuse in DEX-treated cells ( p  = 0.001–0.004). DEX-treated cells showed more senescence compared to controls (~1.7-fold; p  = 0.01–0.02). However, DEX-treated cells did not show increased cross-linked actin network formation or elevated myocilin/fibronectin/α-SMA/phospho-myosin light chain protein expression. For all parameters, MED- and DMSO-treated control cells were not significantly different. Primary scleral fibroblasts, grown from tissue collected immediately distal to the TM, demonstrated scleral-response behaviors that were similar to, but not identical with, classic TM steroid-response. Further study is needed to understand how these scleral cellular alterations may contribute to steroid-response IOP elevation after TM bypass/ablation surgery. Highlights: Distal steroid-response may lead to an increase in intraocular pressure (IOP). Increase in IOP has been observed after trabecular bypass surgery. Scleral fibroblasts steroid-respond similar to trabecular meshwork cells. Steroid-response in AHO pathways may contribute to IOP elevation after MIGS.